2023
DOI: 10.2174/1570159x21666230216094353
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Therapeutics for Alzheimer's Disease: Ancient Indian Medicine System from the Modern Viewpoint

Abstract: Alzheimer's is a chronic neurodegenerative disease where amyloid-beta (Aβ) plaques and neurofibrillary tangles are formed inside the brain. It is also characterized by progressive memory loss, depression, neuroinflammation, and derangement of other neurotransmitters. Due to its complex etiopathology, current drugs have failed to completely cure the disease. Natural compounds have been investigated as an alternative therapy for their ability to treat Alzheimer's disease (AD). Traditional herbs and formulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 113 publications
1
0
0
Order By: Relevance
“…Interestingly, our results demonstrated that CCSB reduced both the release and gene expression of these cytokines, thus supporting the beneficial properties of the blend. This is in line with other reports in which cinnamon and turmeric extract showed anti-inflammatory potential against neurodegeneration [39]. Indeed, curcuminoids are said to be the most potent cytokine-suppressive anti-inflammatory drugs and have a much broader anti-inflammatory action respect to the conventional nonsteroidal anti-inflammatory drugs [40].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our results demonstrated that CCSB reduced both the release and gene expression of these cytokines, thus supporting the beneficial properties of the blend. This is in line with other reports in which cinnamon and turmeric extract showed anti-inflammatory potential against neurodegeneration [39]. Indeed, curcuminoids are said to be the most potent cytokine-suppressive anti-inflammatory drugs and have a much broader anti-inflammatory action respect to the conventional nonsteroidal anti-inflammatory drugs [40].…”
Section: Discussionsupporting
confidence: 91%
“…However, this method is time-consuming and demands a significant amount of labor. The transition to mechanized harvesting has been shown to address these challenges and yield substantial improvements in the agricultural sector [10,11]. Studies have indicated that agricultural mechanization plays a crucial role in the high-quality agricultural development of agriculture, considering that 50% of overall production costs are associated with harvesting [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ashwagandha supplementation has been reported to attenuate cognitive decline associated with inflammation [ 9 , 11 , 12 ] and neurodegeneration [ 8 , 10 , 15 , 23 , 24 , 25 , 26 ]. Since oral ingestion of ashwagandha is bioavailable and crosses the blood–brain barrier [ 24 ], ashwagandha has been considered a naturally occurring therapeutic agent for individuals with type 2 diabetes mellitus [ 9 , 10 , 25 ], mild cognitive impairment [ 8 , 11 , 14 ] and individuals with neurodegenerative diseases [ 14 , 15 , 24 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basic research studies provide a solid theoretical rationale that ashwagandha supplementation may benefit health and cognition [ 25 , 27 , 30 ]. However, fewer studies have evaluated the effects of ashwagandha supplementation on cognitive function in clinical and healthy populations [ 31 ].…”
Section: Introductionmentioning
confidence: 99%